2020
DOI: 10.1007/s42452-020-2273-7
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion studies of stainless steel 304 L in nitric acid in the presence of uranyl nitrate: effect of temperature and nitric acid concentration

Abstract: In order to better understand the role of uranium on the corrosion behavior of stainless in aqueous nuclear fuel reprocessing and decontamination operations, 304L stainless steel coupons were treated with nitric acid media at 45 °C and 90 °C in the presence of 0.3 M of uranyl nitrate. The impact of time, temperature, nitric acid concentration and uranyl nitrate concentration has been studied over a 183 days period and corrosion rates determined. After 183 days, corrosion rates (μm y −1) at 90 °C are: 33.7 ± 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Similarly, previous work by Badet and Poineau showed that the corrosion potential remained within the passive domain for 304L stainless steel held at 45 °C in 8 M HNO 3 for 6 months, with only minor levels of grain boundary etching observed . Despite the lower acidity of the system used in this study, comparable levels of grain boundary etching were seen after 270 days.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, previous work by Badet and Poineau showed that the corrosion potential remained within the passive domain for 304L stainless steel held at 45 °C in 8 M HNO 3 for 6 months, with only minor levels of grain boundary etching observed . Despite the lower acidity of the system used in this study, comparable levels of grain boundary etching were seen after 270 days.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, previous work by Badet and Poineau showed that the corrosion potential remained within the passive domain for 304L stainless steel held at 45 °C in 8 M HNO 3 for 6 months, with only minor levels of grain boundary etching observed. 18 Despite the lower acidity of the system used in this study, comparable levels of grain boundary etching were seen after 270 days. To understand why this occurred, electrochemical potentiodynamic studies were carried out at 50 °C to compare the corrosion potential of the Magnox simulant solution as well as a 1 M HNO 3 reference solution (without contaminants present).…”
Section: Long-term Corrosionmentioning
confidence: 65%
See 1 more Smart Citation